The Analysis of Main Character in Tinker Bell (2008) Movie - Sri Aeni (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
Movie’s story is often connected with the reality of life even though the movie’s character in movie is not human. It is like cartoon movie and fiction movie. Tinker Bell is an interesting cartoon movie. The movie often played by the Indonesian television channel. This study aimed investigated what are Tinker Bell’s personal quality and talent. Tinker Bell’s influence another character in the movie. The population of the study were all of character in Tinker Bell movie. There were : 1) Roseta, 2) Iridesa, 3) Silvermist, 4) Fawn, 5) Fairy Mary, 6) Terence 7)Bobble, 8) Clank, 9)Vidia, 10) Queen Clarion. The sample of the study was the main character in Tinker Bell movie, She was Tinker Bell.The result of the study are 1. Tinker Bell’s personal quality ; Respect, Confidence, Inferiority, Grumpy, Diffidence , Stubborn and Tinker Bell’s talent ; Tinker Fairy talent, Every fairy depend on her talent, Making pots and kettles, Making Nutcracker lever, Making flower sprayer, Making a corn kettles, Creating those gadgets, figuring this out, fixing stuff, Fixing tiny dancer, Fixing and creating somethings from lost things. 2. Tinker Bell’s influence another character; Silvermist, Fawn, Rosetta, Terence, Clank, Bobble, and all of fairy. Keywords: Personal quality; talent; Tinker Bell